CRITICAL APPROACH FOR ‘TO CREATE A MAN’ BY NECIP FAZIL - Rana Gurel, Nazli (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
First of all, Necip Fazıl Kısakürek is one of the most important representatives of the Turkish Drama. Altough to a lesser extent of criticism and impact of Bergson comparing with his first drama Tohum (Seed), his second drama Bir Adam Yaratmak (Creation of a Human) is also a work where the consistency of contemplation, deep questioning and criticism dominate. This drama actually represents a criticism raised against the wrong approach of the press associations which also criticize the artist. In addition, he inculcates the artist to produce, considering the target audience's sense and emphasizes the clout of the word/utterance. Кeywords: Necip Fazıl Kısakürek, To Create a Man, Teater and Critic, Philosophical Process and evidences in Turkish Literature.